Enhancing Student Self-Disclosure Through Instagram Direct Message Counseling: A Prototype Guide for SMKN 7 Malang - Purnamasari, Anggia; Ireni, Pingga Mahsa; Multisari, Widya; Sulistiowati, Dini (Proceedings Series of Educational Studies, 2024)
This study discusses the development of a prototype utilizing direct messaging (Instagram) to enhance self-disclosure among students at SMKN 7 Malang. Self-disclosure is crucial for adolescents, and social media plays a significant role in enhancing self-disclosure and in the field of education, including learning processes and information dissemination. However, social media can also have negative impacts such as addiction and new digital brain behaviors. Schools need to provide quality guidance and counseling services to students to effectively enhance self-disclosure. The approach used in guidance and counseling should emphasize efforts to build quality interpersonal relationships and focus on empowering students to understand the importance of enhancing selfdisclosure. Guidance and counseling services in schools play an essential role as a platform for students to express their feelings and receive professional help. Through counseling services, students can obtain a safe and comfortable space to express concerns, obstacles, or feelings that are difficult to share with others. Counselors will help students develop self-disclosure, thereby allowing them to have self-awareness, make appropriate decisions, and build effective coping strategies. Keywords: prototype development; self-disclosure; counseling platform